Tired of socio-economic stress: socio-demographic contributors to fatigue of mine workers In South Africa - Pelders, Jodi Lyndall (My University, 2020)
Mine workers face hazards both within and outside of the workplace. Challenges with socioeconomic and living conditions prevail in the South African mining industry, and are linked to worker health and wellbeing. Meanwhile, fatigue is an occupational health and safety risk, which can result from hard physical or mental work, health and psychosocial factors, or inadequate sleep. However, there is a lack of research that has assessed the association between demographic and socio-economic characteristics and fatigue. The aim of this research was therefore to fill this gap, and assess socio-demographic contributors to fatigue of mine workers in South Africa. Findings of the research can be used to identify interventions to improve health, safety and productivity in the industry. The research was cross-sectional and employed mixed methods. Data collection took place at 12 mines and one smelter from 2014 to 2017. Qualitative data were gathered through interviews and focus group discussions, with a total of 395 participants, including those in management, labour representatives, and workers. Quantitative data were gathered from questionnaires completed by 1 515 workers. The qualitative data were analysed using thematic analysis. The quantitative data were analysed using descriptive and inferential statistics, including Chi-square tests and binomial logistic regression. Methodological triangulation was used to combine and verify the results from the different sources. The results of the study are contained in four papers published in scientific journals, in fulfilment of the study objectives. The first paper details the living conditions of workers from eight mines in South Africa. The second paper examines associations between sociodemographic factors and health and safety of mine workers. The third paper assesses contributors to fatigue of workers at a platinum smelter. The final paper looks at associations between socio-demographic characteristics and fatigue in the South African gold and platinum sectors. Fatigue was found to be associated with various demographic characteristics, socio-economic and living conditions, and lifestyle, health, safety and wellness factors. In particular, higher levels of fatigue were associated with younger age, higher levels of education, increased commuting times, indebtedness, a lack of exercise, poor nutrition, increased alcohol use, and inadequate sleep. Fatigue was also positively associated with higher levels of stress, poorer health, increased use of sick leave, reduced job satisfaction, and poor quality of life. Multi-stakeholder partnerships, improved employee wellness programmes, enhanced workplace culture, monitoring and evaluation, and further research, are recommended
Original published work submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy (Public Health), 2020